An Evaluation of Indonesian Students’ Self-Confidence in Learning Mathematics - Daud, Muslem; Sariakin, Sariakin; Yusrizal, Yusrizal; Israwati, Israwati; Imran, Imran; Mutia, Ratna (International Conference on Multidisciplinary Research, 2020)
This research aimed to investigate Indonesian students’ self-confidence in learning as one solution for the government to improve Indonesian students’ learning outcomes. The research focused on Math because the evaluation result from Trends in International Mathematics and Science Study (TIMSS) showed that Indonesia was in the 39th position in the world in 2007 for Math Excellence, indicating that more effort needs to be made to improve it. The government has approached this issue by improving the education quality and infrastructure; however, it is also necessary to view it from the psychological perspective, particularly from the students’ self-confidence in learning. This research was qualitative research. It used TIMSS data analyzed with Latent Class Analysis. The research sample was 4403 students of grade eight from 149 Indonesian schools. The findings showed that there are three categories of students’ self-confidence: 1) strong self-confidence (25%), 2) moderate self-confidence (55%), and 3) low self-confidence (20%). Due to a high number of students with a moderate and low level of self-confidence, it is thus advised that the government adopts the psychological approach in education, improve the competencies of teachers and supervisors, and improve teaching and learning methodologies in addition to improving infrastructure so that students’ self-confidence in learning can be increased, and the desired learning outcomes can be achieved. Despite focusing on Math, the findings of this study are also applicable to other subjects. Keywords:  Self-confidence, Self-efficacy, Latent Class Analysis.